An exploration of selected factors affecting the labour market in South Africa - Ralarala, O. S. O.; Mahlangu, C. P. (FMLIC - Conference Proceedings, 2024)
The purpose of this article is to explore selected factors affecting the labour market in South Africa. In the past two decades, South Africa has experienced a great improvement in its labour market, however, the labour market continues to encounter numerous challenges. The article adopted the Auto-regressive Distributive Lag (ARDL) to explore how population, remuneration, and gross fixed capital formation impact the labour market in South Africa for the period 1994 to 2023. A positive relationship between remuneration, population ageing, gross fixed capital formation and the labour market was discovered. To improve South Africa’s labour market, this article proposes that the government invest in programs that enhance technical and vocational abilities. This will facilitate the connection between unemployed youth and sectors requiring skilled labour. This is crucial for mitigating poverty and fostering more inclusivity throughout society. Moreover, this article proposes the implementation of measures aimed at diminishing wealth disparity.
Keywords: Labour market; Population; Remuneration; Gross fixed capital formation; ARDL